Using Body-Conducted Acoustic Sensors for Human-Robot Communication in Noisy Environments. (19th February 2013) - Heracleous, Panikos; Ishi, Carlos T.; Miyashita, Takahiro; Ishiguro, Hiroshi; Hagita, Norihiro
In this study, the use of alternative acoustic sensors in human-robot communication is investigated. In particular, a Non-Audible Murmur (NAM) microphone was applied in tele-operating the Geminoid HI-1 robot in noisy environments. The current study introduces the methodology and the results of speech intelligibility subjective tests when a NAM microphone was used in comparison with using a standard microphone. The results show the advantage of using a NAM microphone when the operation takes place in adverse environmental conditions. In addition, the effect of Geminoid's lip movements on speech intelligibility is also investigated. Subjective speech intelligibility tests show that the operator's speech can be perceived with higher intelligibility scores when the operator's audio speech is perceived along with the lip movements of robots.